Comparative study of Typhidot-M with Widal and blood culture in diagnosis of enteric fever - Udayakumar, S; Pushpalatha, K; Sagar, H M Naveen; Swathi, M; Yoganand, Raksha; Sushma, C (Indian Journal of Child Health, 2017)
Objective: To evaluate the diagnostic utility of Typhidot-M and Widal test in the early diagnosis of enteric fever (EF) in terms of sensitivity and specificity. Methods: The study included 270 children in the age group of 1-18 years admitted to the Department of Pediatrics from November 2012 to February 2014, with fever of 5 days or more and with clinical symptoms and signs suggestive of typhoid fever. Detailed history and clinical examination findings were recorded on a standard pro forma. Complete hemogram (hemoglobin, platelet count, and total and differential leukocyte count), Typhidot-M test, Widal tube test, and blood culture were done on day 1 of admission. For Widal test, a titer of 1 in 160 or more for “O” agglutinins and a titer of 1 in 320 or more for “H” agglutinins were considered as positive results. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated. Results: Of 270 children included in the study, Salmonella typhi was isolated from 82 samples (30.4%) and the remaining 188 (69.6%) were blood culture negative. Widal test was positive in 107 children (39.6%) and Typhidot-M was positive in 136 (50.4%). The sensitivity was 78%, specificity was 79.3%, PPV was 59.8%, and NPV was 91.4% for Widal test. Typhidot-M test had a sensitivity of 81.7%, specificity of 84.6%, PPV of 69.8%, and NPV of 91.4%. Conclusion: Prompt diagnosis of EF is essential for appropriate management and it is, therefore, important to have a satisfactory test to replace conventional tests used for diagnosis. The present study compares newer test (Typhidot-M) against conventional tests such as Widal test and blood culture, and it appears to be a practical alternative to Widal test in the early detection of EF even in the resource-poor laboratories as it neither requires much laboratory equipment nor laboratory expertise to conduct the test. This test can be done within 7 days of illness, but whenever feasible confirmation with blood culture is strongly recommended, especially with the well-documented presence of multidrug-resistant strains of salmonella typhi worldwide. However, both Widal and Typhidot-M appear to correlate less satisfactorily with blood culture, and thus, there is a need for developing a test which allows accurate and early diagnosis of EF to manage a child effectively and limit its morbidity and mortality.